Mouth Dissolving Delivery System: A Novel Approach for Angina - Mishra, Prerana (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The study aims to see the sights of potential of mouth dissolving tablets for improving the oral delivery of nicorandil by the use of superdisintegrants. Materials and Methods: Fast dissolving tablets of nicorandil successfully prepared by direct compression techniques using various concentrations of sodium starch glycolate, croscarmellose sodium, and crospovidone (CP) as superdisintegrants. The optimized batch of fast dissolving tablets of nicorandil were characterized for hardness, friability, in vitro disintegration, dissolution, stability studies. Results and Discussion: In comparison to marketed immediate-release formulation, the formulation (F9) was found to be faster in drug release profile as well as short disintegration time. The formulation F9 were found to be stable in 6 months stability studies in different packing. Conclusion: Nicorandil tablets containing CP as a superdisintegrant show faster disintegration and dissolution rate.